2011
DOI: 10.1002/lary.21870
|View full text |Cite
|
Sign up to set email alerts
|

Association of common variants, not rare mutations, in IRF6 With nonsyndromic clefts in a honduran population

Abstract: This study suggests that common variants, rather than rare mutations, are the cause for association between IRF6 and nonsyndromic CL/P. rs2235371, but not rs642961, shows association with CL/P, suggesting a functional role for this polymorphism in our Honduran population. rs642961 has been previously reported to have an effect in other populations, suggesting that different populations may be affected by different polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
2
11
1
2
Order By: Relevance
“…In contrast to other studies [6], [8][22], all of which showed association of IRF6 comparing only the three major cleft categories (cleft lip, cleft lip/palate and cleft palate), we only found positive association when comparing cleft subphenotypes with controls. Maybe IRF6 is not a strong risk factor for clefting in Brazil, or maybe it has specific contributions, e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies [6], [8][22], all of which showed association of IRF6 comparing only the three major cleft categories (cleft lip, cleft lip/palate and cleft palate), we only found positive association when comparing cleft subphenotypes with controls. Maybe IRF6 is not a strong risk factor for clefting in Brazil, or maybe it has specific contributions, e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Attributable risk calculations suggested IRF6 could contribute to as much as 12% of all cleft cases [6]. Intriguingly, additional studies with different populations have consistently shown positive association between markers in IRF6 and cleft lip/palate [8][22]. The frequency of the V274I risk allele is over 97% in European and African populations making it an unlikely candidate for the etiological mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between the upper lip point and lower lip point (ULipP-LLipP) also suggested potential shape difference between the CC and TT groups (nominal p value = 0.0023, Table 2). The suggestive involvement of this SNP with mouth shape is consistent with the known role the host gene IRF6 plays in NSCL/P [17], [23], [44], [45]. SNP rs6180 and rs6184 both showed some signals in males, which seemed to mainly involve the two lip corners and their relative positions to the middle line landmarks such as Pronasale, Nasion, Subnasale, lower lip point and chin (Table 2).…”
Section: Resultssupporting
confidence: 79%
“…The Interferon regulatory factor 6 ( IRF6 ) plays a critical role in keratinocyte development. Genetic variants of IRF6 , especially SNP rs642961, were found consistently associated to NSCL/P throughout many candidate gene and GWAS studies [17], [23], [44], [45] As the genetic risk factors of NSCL/P may also contribute to normal facial variation in healthy carriers [16], we enrolled rs642961 into our study. We further included the SNP rs2236907 of IRF6 , which seems to have a particularly strong signal in Han Chinese [23], [46].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, one European and two non-European studies did not identify any association between this variant and nsCL/P (ref. [25][26][27] ). Another finding of our study was an association of the SNP located at the 8q24 locus with nsCL/P.…”
Section: Discussionmentioning
confidence: 99%